Laying the Foundation: Practicing Before Teaching in Structured Literacy - Joan Sinagra Brillant (The Advocate, 2026)
The preparation of elementary pre-service teachers to deliver effective Structured Literacy instruction is critical for improving early reading outcomes, particularly for students with reading difficulties. This study examines how undergraduate elementary education pre-service teachers will enhance their instructional effectiveness in Structured Literacy lessons by practicing lessons and activities in class with their peers prior to teaching in the elementary classroom. This study investigates changes in pre-service teachers’ thoughts, instructional planning, and implementation of explicit, systematic, and multisensory literacy lessons throughout their undergraduate course work as they develop, plan, and teach elementary literacy lessons. Using a qualitative design, data sources include survey questions and observations of in class lessons. Implications suggest that embedding high-quality instructional practices through hands-on experiences in teacher preparation programs pre-service teachers’ instructional effectiveness will improve and they will be better equipped to meet the diverse literacy needs of elementary learners.
Keywords: Pre-service Teachers; Structured Literacy; Literacy; Phonics; Multimodal Lessons